The relationship between alcohol consumption and related harm among young university students - Hart, E.; Burns, Sharyn (John Wiley & Sons, 2016)
Issue addressed: Research has shown that Australian university students consume alcohol at a higher level than their peers from the general population and are therefore more likely to witness and experience alcohol-related harm. This study measured the prevalence of alcohol consumption among 18–24-year-old university students and the association between alcohol consumption and witnessed and experienced harms. Methods: A random cross-sectional sample of university students aged 18–24 years (n = 2466) was recruited via the University Survey Office and through random intercept at campus market day. All participants completed an online survey that included the Alcohol Use Disorders Identification Test, Alcohol Problems Scale and an additional scale measuring witnessed harm. Results: Principal Components Analysis revealed three factors within the Alcohol Problems Scale; i.e. Criminal and Aggressive Behaviour, Health and Emotional Harms and Sexual Harms. Students who consume alcohol at high-risk levels were significantly more likely to score highly on each factor, 1.6 times more likely to experience harm and 1.1 times more likely to witness harm than students who consume alcohol at low-risk levels. Conclusions: The positive association between alcohol consumption and alcohol-related harm supports previous findings. This study adds previous research through the categorisation of harm into factors.